Leadership Quality in the Millennial Era in Achieving Organizational Goals - Abdul Aziz; Ratni Prima Lita; Rida Rahim; Veri nita (Inovbiz: Jurnal Inovasi Bisnis Seri Manajemen, Investasi dan Kewirausahaan, 2023)
Becoming a leader in the era of the industrial revolution and the evolution of society or better known as the millennial era requires a different leadership style. George Bradt said, "Don't even try to manage Millennials but lead them". The basic concept of this journal is extracted from the results of a review of 5 (five) International Journals and is supported by articles and other relevant journals. The important thing that a leader needs to understand is knowledge which includes science, morals and art. Science will determine what is right and wrong, morals will determine good and bad, and art will determine what is beautiful and ugly. All of that will be a good aesthetic if a leader collaborates with each other, especially in carrying out work programs in achieving organizational goals. Schnatterly et al. (2018) says that a good leader is an ethical servant who arouses high commitment from his followers. Meanwhile, Oboh et al. (2020) states that honesty, integrity, trust, and courtesy are some of the manifestations of ethical values that must be owned and carried out by leaders, including when the leader runs a business.